(untitled) (Journal of Philosophy Culture and Political Science, 2023)
The research clearly identified a majority of young people constantly leave Kazakhstan to work in foreign countries. This problem can be solved by developing social conditions for working and studying which retain the youth in our country. For context, the experience of foreign and domestic scientists was analyzed in our article. In order to understand the underlying issues raised in this study we should consider the life principles and ideas of youth development which currently exist in our country. This study has brought to our attention the key problems of state policy in the field of youth migration, the need to identify issues that concern young migrants so that future decision-making can target the elimination of social attitudes and problems which cause youth migration. The study developed recommendations to be directed at the government, local executives, representative bodies and civil society organizations, with a view addressing the problems faced by young people, which are sources of social tension and lead to migration. The research showed that the majority of migrants do not have membership of pension funds and are excluding from the provision of social welfare benefits and allowances for themselves and their children. More than five hundred respondents and students aged from 18 to 28, from different regions of the country, were interviewed as part of the research. A comparative analysis of statistical data of young people working abroad was also conducted. The main reasons and consequences of the departure of the youth of Kazakhstan abroad were therefore determined. The practical significance of this research is that it be used when discussing and resolving the issue of youth migration in the subject areas of political science and sociology. Key words: Youth of Kazakhstan, internal migration, education abroad, global integration, social support